Social Capital and Economic Development 2002
DOI: 10.4337/9781781950388.00010
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Well-being in Developing Countries: An Introduction

Abstract: What are human investments? Can they be distinguished from consumption? Is it at all feasible to identify and measure them? What do they contribute to income? Granted that they seem amorphous compared to brick and mortar, and hard to get at compared to the investment accounts of corporations, they assuredly are not a fragment; they are rather like the contents of Pandora's box, full of difficulties and hope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 13 publications
(14 reference statements)
1
26
0
3
Order By: Relevance
“…A growing strand of literature has emphasized the fundamental importance of social capital for subjective well-being (Putnam 2000;Isham et al 2002;Helliwell 2006;Yip et al 2007). Putnam et al (1993) conducted a natural experiment by studying the institutional performance of Italian regions from 1970s onwards when Italian government established regional governments and showed that differences in contemporary institutional efficacy between the North and South (Mezzogiorno) can be traced back to the differences in various components of social capital such as trust in others, association and civic traditions that extend back to the Middle Ages.…”
Section: Happiness: Causes and Correlatesmentioning
confidence: 99%
“…A growing strand of literature has emphasized the fundamental importance of social capital for subjective well-being (Putnam 2000;Isham et al 2002;Helliwell 2006;Yip et al 2007). Putnam et al (1993) conducted a natural experiment by studying the institutional performance of Italian regions from 1970s onwards when Italian government established regional governments and showed that differences in contemporary institutional efficacy between the North and South (Mezzogiorno) can be traced back to the differences in various components of social capital such as trust in others, association and civic traditions that extend back to the Middle Ages.…”
Section: Happiness: Causes and Correlatesmentioning
confidence: 99%
“…Por ejemplo, Reyes (1999) y Collier (2002 enfatizan el papel de la acción de los grupos armados en el aumento de la pobreza, y Cárdenas (2002) explica la caída en el crecimiento del ingreso colombiano en los últimos años con una implosión de productividad que se explica por el aumento del crimen, el fortalecimiento de los movimientos insurgentes y la expansión del narcotráfico a inicios de los años ochenta. En las dos últimas décadas, la medición del capital social se ha constituido en un debate reconocido (Isham et al, 2002;Atria et al, 2003;Dasgupta y Serageldin, 2000). Éste se ha enriquecido con diferentes metodologías y aproximaciones empíricas al concepto de capital social, sus alcances y formas y los diferentes canales en los que facilita el desarrollo (Grootaert y Van Bastelaer, 2002).…”
Section: Costos Del Capital Socialunclassified
“…So far, the studies on social capital in developing countries have been mostly oriented toward the economic and political effects of social capital (ISHAM et al, 2002;TENDLER, 1997) and only a few analyses have examined the mechanisms through which these effects happen.…”
Section: State-civil Society Partnership: Issues For Debate and New Rmentioning
confidence: 99%
“…According to Isham et al (2002), only a few studies about societies deprived of trust have underlined the role of social capital in overcoming market failures and building democracy. So far, the studies on social capital in developing countries have been mostly oriented toward the economic and political effects of social capital (ISHAM et al, 2002;TENDLER, 1997) and only a few analyses have examined the mechanisms through which these effects happen.…”
Section: State-civil Society Partnership: Issues For Debate and New Rmentioning
confidence: 99%